THE EFFECT OF BOND RATING, DEBT TO EQUITY RATIO, LIQUIDITY, AND SBI INTEREST RATES ON CORPORATE BOND YIELD TO MATURITY - Mega Wati; Muhamad Helmi; Destia Aktarina; Debi Carolina (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
Judging from Indonesia's investment opportunities every year, the average investment opportunity has increased from year to year. This proves that Indonesia's investment activities should be given primary attention, both when the country's economy is deteriorating and when the country's economy is improving. The aim of this research isto determine the development of bond ratings, debt to equity ratio, liquidity, SBI interest rates on the yield to maturity of corporate bonds listed on the IDX for the 2017-2021 period and to determine the influence of bond ratings, debt to equity ratio, liquidity, SBI interest rates partially and simultaneously on the yield to maturity of corporate bonds.The analytical method used is the descriptive method and verification method with a sample of 7 companies. The results show that partially the bond rating and SBI interest rate variables have a positive and significant effect on yield to maturity, while the debt to equity ratio and liquidity variables have no significant effect on yield to maturity and simultaneously there is at least one independent bond rating variable, debt to Equity ratio, liquidity and SBI interest rates influence the yield to maturity of corporate bonds. This conclusion provides important insight into the factors that can influence the yield to maturity of corporate bonds on the IDX, which can be a guide for market players and companies in making financial decisions.